Using kolb's learning model in structured types of professional education and training for teachers - Snježana Močinić; Sanja Tatković (University of Maribor Press, 2021)
The use of Kolb's model enhances the effects of professional development because the model allows the exchange of concrete experience, reflective observation, abstract conceptualisation and active experimentation, and provides the connection between theory and practice. The empirical part of this paper analyses the results of a survey conducted among teachers from Croatian primary schools regarding the presence of the four stages of Kolb's learning model in structured types of professional education and training. The survey shows teachers' dissatisfaction regarding the presence of activities such as reflection on teaching, linking theory to practice and stimulating research activities in teaching practice.